Cost-efficient production of in vitro Rhizophagus irregularis - Rosikiewicz, Pawel (Mycorrhiza, 2017)
One of the bottlenecks in mycorrhiza research is that arbuscular mycorrhizal fungi (AMF) have to be cultivated with host plant roots. Some AMF species, such as Rhizophagus irregularis, can be grown in vitro on dual-compartment plates, where fungal material can be harvested from a fungus-only compartment. Plant roots often grow into this fungus compartment, and regular root trimming is required if the fungal material needs to be free of traces of plant material. Trimming also increases unwanted contamination by other microorganisms. We compared 22 different culture types and conditions to a widely used dual-compartment culture system that we refer to as the “standard system.” We found two modified culture systems that allowed high spore production and low rates of contamination. We then compared the two modified culture systems with the standard system in more detail. In the two modified culture systems versus the standard system, a comparable number of spores were produced per plate, the necessity for root trimming was reduced, and there was significantly diminished contamination in the fungal compartment. A cost analysis showed that both modified culture systems were more economic than the standard culture system for the production of the same number of non-contaminated spores. The two modified culture systems provide an economic alternative for the production of contaminant-free fungal material which is ideal for studies requiring AMF DNA or RNA for genetics, genomics, and transcriptomic studies or for studies requiring relatively large amounts of fungal material for greenhouse experiments. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00572-017-0763-2) contains supplementary material, which is available to authorized users.